PERAN ORANG TUA DALAM MENERAPKAN POLA ASUH KEBIASAAN ADAT DAYAK TUNJUNG "POJEEQ" TERHADAP ANAK DI DUSUN PUTAK, KALIMANTAN TIMUR - Lestari, Ela; Bintang, Dian Wahyu Putri; Putri, Feby Purisda; Karlina, Pipi; Putri, Maya Angeli Yulia; Rozie, Fachrul (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2024)
The parenting pattern of each family in Indonesia must be different, because of the diversity of their tribes. This parenting style is a way of educating children with the encouragement to change children's behavior, knowledge, and values that are considered appropriate in a society. The purpose of this study was to find out how the role of parenting in the traditional customs of Dayak Tunjung Pojeeq or puhunan in Putak Hamlet, East Kalimantan. The research method used is to use a qualitative approach method. By using a planned interview technique, the interviewer prepares an interview guideline and makes direct observations. The results of this study can be concluded that the parenting style of parents in the application of Pojeeq habits  is still many parents who have not applied it, plus most of the parents do not believe in the existence of Pojeeq. This is also supported by the development of the times and increasingly sophisticated technology, so that things that are beyond reason are difficult to understand and accept by today's children.